The safety and efficacy of xanthan gum-based thickeners and their effect in modifying bolus rheology in the therapeutic medical management of dysphagia - Enrico K. Hadde (Elsevier, 2021)
Thickened fluids are commonly prescribed for the medical management of individuals who have swallowing difficulty. However, it is not always easy to obtain the prescribed thickness consistency of thickened fluids and, a common contributor to variabilities in thickness consistency is the type of thickener selected. Xanthan gum-based thickeners are increasingly used in commercial thickening products for management of oropharyngeal dysphagia (OD). While less common, xanthan gum-based thickening agent in a liquid form is an alternative thickening agent for use only under medical supervision for the management of OD. It is hypothesised that liquid thickener is substantially equivalent in safety and therapeutic function to xanthan gum-based powdered thickener. This systematic review aims to identify the safety and efficacy of powdered and liquid xanthan gum-based thickeners and their effect in modifying bolus rheology in the therapeutic medical management of OD. A multi-engine search yielded 210 non-duplicate articles of which 43 were judged to be relevant. The articles underwent detailed review for study quality and data extraction that confirmed xanthan gum-based thickened fluids are effective in improving the safety of swallow and reduce aspiration without increasing the prevalence of pharyngeal residue. Additionally, xanthan gum-based thickeners are superior to starch-based because of better texture perception, more cohesive, better stability (e.g., time or temperature) and better resistance to salivary amylase. Both forms (liquid or powder) of thickener are clinically safe and effective in improving the swallow safety in individuals with OD, although published clinical data supporting the safety and efficacy of liquid xanthan gum is more limited. However, in some situations, liquid form is more suitable than powdered alternatives because it is more readily dissolves directly in the fluid, although to date, there are no published clinical trials supporting the safety and efficacy of liquid xanthan gum.